Design and delivery of national housing in the UAE: an alternative approach - Mohamed, Basem Eid; Elkaftangui, Mohamed; Zureikat, Rana; Hiyasat, Rund (Frontiers in Built Environment, 2023)
The provision of national housing to citizens in the United Arab Emirates (UAE) is considered as a crucial topic. Over the course of the past four decades, the process of developing national housing has emerged into multiple housing programs and schemes, all with the same aim of offering affordable, and high-quality housing to citizens, in addition to the needs of local families regarding spatial configurations while maintaining cultural values. However, despite all these efforts, the question has always remained: are offered housing practices suited for family needs, ever socio-economic trends, and environmental challenges? This paper aims to offer an alternative approach for the design and delivery of national housing practices in the UAE. The proposed process is structured based on the following ethos. First, a conceptual framework for design flexibility towards offering customization, while maintaining contextual and cultural qualities for inhabitants. Second, a computational design strategy for façade optimization that illustrates the significance of incorporating environmentally- conscious design strategies in response to local climatic conditions, towards enhancing overall building performance. Thirds, a hybrid production model that relies on prefabricated building approach that combines precast concrete systems with 3D printing technology. The efforts described in this paper represent a significant phase of an ongoing research endeavor that explores how technological capacities could help rethink national housing in the UAE.